Analisis Kemampuan Komunikasi Matematis Terhadap Kemampuan Self-Concept Siswa SMP - Nursanti Nursanti; Fauziah Hakim; Rezki Amaliyah AR (SUPERMAT : Jurnal Pendidikan Matematika, 2022)
This research was a mixed method which aimed to determine the effect of mathematical self-concept on mathematical communication skills and to describe mathematical communication skills in relation to mathematical self-concept. This research was conducted at SMP Negeri 2 Majene in the even semester of the 2021/2022 academic year. The subjects in this study amounted to 9 students of class VIII A SMP Negeri 2 Majene. The research design used was quantitative explanatory with descriptive method. The instruments in this study were tests, questionnaires, and interview guidelines. The data analysis technique used was quantitative analysis and qualitative analysis. The results of this study indicated that there was a positive and significant effect between mathematical self-concept and students' mathematical communication skills. In addition, this study also showed that subjects with high mathematical self-concept tend to be able to fulfill all indicators of mathematical communication skills including grammar skills, discourse skills, sociolinguistic abilities, and strategic abilities. Subjects with moderate mathematical self-concepts tend to be able to fulfill 3 indicators including grammar skills, discourse skills, and sociolinguistic abilities. The strategic ability indicator has not been met because the subject gave the wrong answer and was not able to explain the stages of completion. Subjects with low mathematical self-concept tend not to be able to fulfill all indicators of mathematical communication skills including grammar skills, discourse skills, sociolinguistic abilities, and strategic abilities.